Early Active Irrigation-Suction Drainage among Enterocutaneous Fistulas Patients with Chronic Critical Illness: A Retrospective Cohort Study. Issue 4 (April 2020) - Jiang, Zhizhao; Ren, Jianan; Ren, Huajian; Hong, Zhiwu; Wang, Gefei; Gu, Guosheng; Wu, Xiuwen
Enterocutaneous fistulas (ECFs) requiring admission to ICU is a serious surgical complication. A growing number of patients survive ECFs but remain chronically critically ill. The aim of our study was to investigate the risk factors of hospital death in patients with chronic critical illness attributed to ECFs. A retrospective single-center study was conducted in 163 ECF patients between 2013 and 2017. Patient-specific baseline characteristics, outcomes, and process of care variables were collected. Risk factors for hospital mortality were determined using univariate and multi-variate analyses. Patients were divided into the following two groups according to the hospital discharge outcome: group survivors (n = 106) and group nonsurvivors (n = 57). Patients who received active irrigation-suction drainage (AISD) within 24 hours after the diagnosis of ECFs had a significantly lower hospital mortality rate than those who received AISD after more than 24 hours (17.9% vs 46.9%, P < 0.001). Multivariate logistic regression analysis demonstrated that delayed AISD (adjusted odds ratio [AOR], 10.24; 95% confidence interval [CI], 3.03234.59; P < 0.001) and no rehabilitation therapy (AOR, 4.77; 95% CI, 1.43215.98; P = 0.011) were independently associated with a greater risk of hospital mortality. The hospital mortality rate in patients with more than or equal to four risk factors was 92.6 per cent (n = 57), compared with a mortality rate of 9.4 per cent (n = 106) in patients who did not have these risk factors ( P < 0.001). The risk of hospital death is exceptionally high among patients with chronic critical illness attributed to ECFs. Efforts aimed at early AISD and rehabilitation therapy are likely to be associated with improved clinical outcomes.